Investigating the tensile cracking mechanisms of rock masses containing random fissures from the perspective of meshless numerical method - Chen, Jinyu; Sun, Yi; Li, Wei; Zhang, Bufan; Yu, Shuyang (Frontiers in Earth Science, 2025)
This paper focuses on the tensile cracking mechanisms of rock masses containing random fissures and conducts research based on the meshless numerical method. In view of the shortcomings in traditional research on rock crack propagation, such as the difficulty of experiments in reflecting stress changes, the inapplicability of theoretical research to complex geometric conditions, and the limitations of existing numerical simulation methods, this paper proposes an improved Smooth Particle Hydrodynamics (SPH) method. The traditional SPH smooth kernel function is re-written, a parameter к that can represent particle failure is introduced, the Mohr-Coulomb criterion is combined to judge particle failure, and the control equations are updated to simulate the progressive failure processes of particles. Under the SPH framework, the Monte Carlo method and the linear congruence method are used to develop a random fissure generation algorithm, which can effectively simulate the real distribution of random fissures inside rock masses. By simulating the crack propagation process under uniaxial tensile stress with different fissure lengths, numbers, and dip angles, the mechanical behaviors of random fissure rocks during the tensile process are analyzed in depth. The results show that an increase in fissure length makes cracks more likely to occur and changes the failure mode; Variations in fissure angles affect the crack propagation paths and the dominant final failure morphologies; An increase in the number of fissures changes the failure mode from simple crack penetration to complex fragmentation. At the same time, the stress-strain curves under different schemes are analyzed, and the influence laws of fissure characteristics on the elastic modulus and peak strength of rocks are clarified. The research results provide a new perspective for understanding the mechanical behavior of rocks under tensile loads and offer theoretical and numerical references for the analysis and design of tensile failure problems in geotechnical engineering. In addition, the application prospects and limitations of the SPH method in rock fracture simulation are discussed, and it is pointed out that future research should focus on developing 3D parallel programs to more accurately simulate the real rock fracture process and contribute to the development of geotechnical engineering theory and practice.